Hypovitaminosis D is an independent associated factor of overactive bladder in older adults. (July 2016) - Kilic, Mustafa Kemal; Kizilarslanoglu, Muhammet Cemal; Kara, Ozgur; Arik, Gunes; Varan, Hacer Dogan; Kuyumcu, Mehmet Emin; Yesil, Yusuf; Yavuz, Burcu Balam; Halil, Meltem; Cankurtaran, Mustafa
Highlights: Urinary incontinence is a common problem among geriatric population. The precise mechanism is still unknown. Sufficient daily vitamin D synthesis is of utmost importance in terms of many medical issues. Recent studies ascribe vitamin D a role in bladder physiology. Results of this study emphasize the role of vitamin D in bladder physiology leading to urgency urinary incontinence. Abstract: Aim of the study: Urinary incontinence and vitamin D deficiency are common problems encountered in geriatric population. We aimed to investigate if there is a relationship between these conditions. Subjects and method: Among 2281 patients who were admitted to our geriatric medicine outpatient clinic spanning the last three years, 705 patients with known vitamin D status, urinary incontinence and subtype, and calcium plus vitamin D therapy data were included in statistical analysis. Patients who are using calcium plus vitamin D therapy were excluded. SPSS (Statistical Package for Social Sciences) version 15.0 for Windows was used for statistical analysis and p < 0.05 was considered as statistically significant. Results: Mean age of the study population was 72.3 ± 6.4 years and 62.8% were female. Plasma vitamin D level (OR: 0.968, 95%CI: 0.943–0.993, p = 0.013), MMSE (Mini Mental State Examination) score (OR: 0.944, 95%CI: 0.902–0.989, p = 0.014), and serum ALP (Alkaline Phosphatase) level (OR: 0.995, 95%CI: 0.992–0.998, p = 0.001) were found to be inversely correlated factors, and serum calcium level (OR: 1.772, 95%CI: 1.008–2.888, p = 0.022) was found to be a positively correlated factor of overactive bladder. Considering the different clinical subtypes of urinary incontinence, only urgency incontinence was associated with lower plasma vitamin D level (p = 0.013). Conclusions: Vitamin D deficiency and insufficiency are independent associated factors for overactive bladder in older adults. This is explicable by effects of vitamin D on muscle growth and function.